2023
DOI: 10.1111/coa.14064
|View full text |Cite
|
Sign up to set email alerts
|

The assessment and management of deep neck space infections in adults: A systematic review and qualitative evidence synthesis

Abstract: Objectives: To summarise current practices in the diagnosis and management of deep neck space infections (DNSIs). To inform future studies in developing a framework in the management of DNSIs.Design: This review was registered on PROSPERO (CRD42021226449) and reported in line with PRISMA guidelines. All studies from 2000 that reported the investigation or management of DNSI were included. The search was limited to English language only. Databases searched included AMED, Embase, Medline and HMIC. Quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 95 publications
2
3
0
Order By: Relevance
“…The ndings highlight the importance of early recognition and appropriate management to prevent the development of life-threatening complications. [2,10,14] Consistent with previous studies, odontogenic infections were identi ed as the most common etiology of DNIs. [1,8,10,15,16] This underscores the importance of dental hygiene and timely treatment of dental infections to prevent the spread of infection to deeper neck spaces.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The ndings highlight the importance of early recognition and appropriate management to prevent the development of life-threatening complications. [2,10,14] Consistent with previous studies, odontogenic infections were identi ed as the most common etiology of DNIs. [1,8,10,15,16] This underscores the importance of dental hygiene and timely treatment of dental infections to prevent the spread of infection to deeper neck spaces.…”
Section: Discussionsupporting
confidence: 85%
“…[2,10,14] Consistent with previous studies, odontogenic infections were identi ed as the most common etiology of DNIs. [1,8,10,15,16] This underscores the importance of dental hygiene and timely treatment of dental infections to prevent the spread of infection to deeper neck spaces. [17] In our study, the microorganisms isolated were Klebsiella pneumoniae, Staphylococcus spp., and Viridans streptococcus, whereas previous studies have also demonstrated that S. pyogenes, S. aureus, Streptococcus viridans, and Haemophilus in uenza are the most common bacterial species.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Traditionally, the main treatment method for DNAs is complete surgical incision and drainage with appropriate administration of antibiotics. [14][15][16][17][18][19] However, surgical drainage has several drawbacks. First, the risk of inadvertent injuries to neighbouring vital structures (including the internal jugular vein, carotid artery and cranial nerves)…”
Section: Introductionmentioning
confidence: 99%